EVALUATION OF CONTINUOUS AND WATER ALTERNATING GAS (WAG) CO2 INJECTION ON X FIELD RECOVERY FACTOR - Ababil, Pijar Fitrah; Hadziqul Abror,; Riska Laksmita Sari, (Journal of Earth Energy Engineering, 2023)
Indonesia is a country rich in natural resources. The wealth of Indonesia's natural resources is not only limited to agricultural and plantation products, but also from mineral and hydrocarbon mining or oil and gas. Indonesia's oil production has continued to decline in the last 10 years until the national consumption rate is much higher than national production. One of the causes of the decline in oil production in Indonesia is the condition of Indonesia's oil fields, which are currently mature fields. To overcome the problem of old fields that still have economic oil reserves, enhanced oil recovery (EOR) can be used. One of the EOR methods that can be used is the CO2 injection method using continuous and WAG injection schemes. The study was conducted in X field with oil-wet carbonate rock composition with waterdrive and fluid expansion driving mechanism. The basecase production scheme using 5 production wells produces a recovery factor of 34.3%, while continuous CO2 injection produces a recovery factor of 32%, and CO2-WAG produces a recovery factor of 42%. Continuous CO2 injection has the lowest recovery factor because early gas breaktrough occurs due to a large mobility ratio and causes gas fingering, hindering the oil production process. The most suitable injection method is CO2-WAG 1 cycle using a 1:1 ratio, CO2 injection volume of 6.661 MSCF/D, injection water volume of 37.4 MBBL/D with a recovery factor of 43.46%.